IMPACT OF FUNDAMENTALS OF PEACE EDUCATION AMONG STUDENTS’ COGNITIVE AND BEHAVIOURAL ASPECTS AT MINDANAO STATE UNIVERSITY GENERAL SANTOS CITY - Mohammad Borhan H. Emam, Kominie S. Ansa, Nurshia R. Salih, Noraisa A. Mama (PRODI PAI FIK UNIRA MALANG, 2026)
This study examines the effects of peace education fundamentals on the cognitive and behavioural characteristics of Mindanao State University-General Santos City students. A non-profit process, specifically a proportionate sampling technique, was employed to identify the respondents, and a questionnaire was utilized to collect the necessary data. A descriptive survey method was used. Frequency, mean, and grand mean are the statistical techniques used in data analysis. According to this study, students can comprehend the general objectives of the FPE101 subject since they have a high level of understanding of the subject's goal of resolving conflicts amicably (grand mean 4.46). With a grand mean of 4.03, the cognitive impact on students' understanding of peace concepts in Islam, other religions, and spiritual traditions is quite strong since they are able to identify similarities in the ideas of peace across different faiths. Additionally, students have a high level of knowledge about conflict and violence because they can recognize the value of determining the root cause of a conflict. Additionally, students' cognitive understanding of conflict resolution has a grand mean of 4.03 because they are developing their active listening skills. Nonetheless, upon their completion of FPE101, students consistently advocate for universal ideals that are pertinent to them. The students suggest enhancing the FPE101 course by supplying additional reading resources focused on peace education and creating chances for intercultural interactions among Indigenous Peoples, Muslims, and Lumads within the university.